Berkhotbah dengan Kuasa: Pembacaan Matius 5-7 dari Perspektif Pentakostal - Harseno, Han Denny (Jurnal Teologi Berita Hidup, 2025)
Matthew chapters 5-7 are commonly called the Sermon of Christ on the Mount. The opening (Matt. 5:1-2) and concluding verses (Matt. 7:28-29) affirm that Jesus taught with divine authority. Through a qualitative method with a literature review approach, this article interprets both passages from a Pentecostal point of view, relating them to homiletics. The findings of the study show that the delivery of the word is not just a human task, but an act of divinity because: the Holy Spirit anoints the preacher, the preacher has spiritual authority, and the powerful preaching causes wonder. The authority in the teaching of Jesus, became the inspiration for the powerful sermons of the Pentecostals. Its implications for today's homiletics include: balancing biblical exegesis with spiritual readiness, delivering sermons with divine authority, and a style of preaching that is responsive to the work of the Holy Spirit.